The Relationship between Pregnant Women's Knowledge and the Incidence of Preeclampsia - Siregar, Nurhapsah (Benih : Journal of Midwifery, 2022)
Preeclampsia is a clinical syndrome that often occurs during pregnancy, characterized by hypertension, proteinuria, and edema after 20 weeks of gestation. Pregnant women's knowledge about this condition can affect early detection and proper management. This study aims to evaluate the relationship between pregnant women's knowledge and the incidence of preeclampsia. Methods: Descriptive study was conducted in RSUD Panyabungan, Mandailing Natal Regency. A total of 34 pregnant women were the subjects of the study. Data were collected through a questionnaire that measured the level of knowledge of pregnant women about preeclampsia. Statistical analysis was performed to determine the relationship between knowledge variables and the incidence of preeclampsia. Results: The majority of respondents had sufficient knowledge (55.9%), followed by good (23.5%) and poor (20.6%) knowledge levels. Statistical analysis showed a significant association between the knowledge of pregnant women and the incidence of preeclampsia (p < 0.05). However, no significant association was found between knowledge and risk factors such as age and parity (p > 0.05). Conclusion: Knowledge of pregnant women is associated with the incidence of preeclampsia. Education and counseling efforts to pregnant women need to be increased to improve their understanding of preeclampsia, so as to improve early detection and management of the condition.